Isolated States of America: The impact of state borders on mobility and regional labor market adjustments - Riley Wilson (W.E. Upjohn Institute for Employment Research, 2021)
I document a new empirical pattern of internal mobility in the United States. Namely, county-tocounty migration and commuting drop off discretely at state borders. People are three times as likely to move to a county 15 miles away, but in the same state, than to move to an equally distant county in a different state. These gaps remain even among neighboring counties or counties in the same commuting zone. This pattern is not explained by differences in county characteristics, is not driven by any particular demographic group, and is not explained by pecuniary costs such as differences in state occupational licensing, taxes, or transfer program generosity. However, county-to-county social connectedness (as measured by the number of Facebook linkages) follows a similar pattern. Although the patterns in social networks would be consistent with information frictions, nonpecuniary psychic costs, or behavioral biases such as a sate identity or home bias, the data suggest that state identity and home bias play an outsized role. This empirical pattern has real economic impacts. Building on existing methods, I show that employment in border counties adjusts more slowly after local economic shocks relative to interior counties. These counties also exhibit less in-migration and in-commuting, suggesting the lack of mobility leads to slower labor market adjustment.
Keywords: J6; R1; 330; Internal migration; commuting; social networks; border discontinuities